Ansible 2 Cloud Automation Cookbook : Write Ansible playbooks for AWS, Google Cloud, Microsoft Azure, and OpenStack. - Aggarwal, Vikas (Packt Publishing, 2018)
Ansible is a powerful and versatile tool used for configuration management and orchestration. Ansible's usefulness is derived from its modules. This book focuses on modules that will help you provision cloud resources by interacting with various APIs exposed by cloud providers. Taking a step further, you will learn how to manage cloud ...